2019
DOI: 10.1111/1348-0421.12666
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a new real‐time RT‐PCR assay for detecting the latest H9N2 influenza viruses capable of causing human infection

Abstract: The H9N2 subtype of avian influenza A viruses (AIV) has spread among domestic poultry and wild birds worldwide. H9N2 AIV is sporadically transmitted to humans from avian species. A total of 42 laboratory‐confirmed cases of non‐fatal human infection with the Eurasian Y280 and G1 lineages have been reported in China, Hong Kong, Bangladesh and Egypt since 1997. H9N2 AIV infections in poultry have become endemic in Asia and the Middle East and are a major source of viral internal genes for other AIV subtypes, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…The genetic analysis of recent H9N2 sequences revealed adaptive mutations from avian-like to human-like receptor binding, indicating the capacity to readily infect new hosts without prior adaptation [ 31 , 32 ]. Most of the H9N2 human infections were reported simultaneously with H9N2 influenza virus detection in local poultry, and were mainly due to close contact with poultry [ 33 , 34 , 35 ]. Seromonitoring of synanthropic species such as crows and sparrows may be useful to understand their role in avian influenza ecology.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic analysis of recent H9N2 sequences revealed adaptive mutations from avian-like to human-like receptor binding, indicating the capacity to readily infect new hosts without prior adaptation [ 31 , 32 ]. Most of the H9N2 human infections were reported simultaneously with H9N2 influenza virus detection in local poultry, and were mainly due to close contact with poultry [ 33 , 34 , 35 ]. Seromonitoring of synanthropic species such as crows and sparrows may be useful to understand their role in avian influenza ecology.…”
Section: Discussionmentioning
confidence: 99%
“…Among these cases, 17 infections were documented during 1999 to 2012, 28 cases were reported from 2013 to present, showing increasing tendency in recent years (Figure ). Epidemiological and virologic evidences showed that all H9N2 viruses isolated from human were of avian origin and genetically similar with those prevalent in the local poultry (Cheng et al, ; Saito et al, ). In addition to China, H9N2 human infections were also reported in Oman, Pakistan, India, Bangladesh and Egypt, where avian H9N2 influenza viruses were detected and prevalent in the poultry at the same time (Shanmuganatham et al, ; Sun & Liu, ; Website of WHO).…”
Section: Current Status Of H9n2 Infection In Humanmentioning
confidence: 99%
“…Development and evaluation of a new one-step, real-time RT-PCR assay was developed for detecting latest H9N2 influenza viruses competent of causing human infection. The sensitivity of one-step, real-time RT-PCR assay was generally determined to be used in vitro transcribed RNA, devoid of any cross-reactivity against RNA from H1-15 subtypes of influenza viruses and other viral respiratory pathogens with no nonspecific reactions (Saito et al 2019).…”
Section: Pcr/rt-pcr-based Immunodetectionmentioning
confidence: 99%